A parametric sensitivity analysis for prioritizing regolith knowledge needs for modeling water transfers in the West African critical zone. Issue 6 (16th November 2021) - Herzog, Amelie; Hector, Basile; Cohard, Jean‐Martial; Vouillamoz, Jean‐Michel; Lawson, Fabrice Messan Amene; Peugeot, Christophe; de Graaf, Inge
Abstract: Hard rock aquifers (HRAs) in West Africa (WA) are located within a thick regolith layer. The representation of thick tropical regolith in integrated hydrological models lacks consensus on aquifer geometries and parameter ranges. Our main objective was to determine the knowledge requirements on saturated hydraulic conductivity ( K s ) to model the critical zone (CZ) of HRAs in WA. A parametric sensitivity analysis with a focus on the representation of the K s heterogeneity of the regolith was conducted with a critical zone model (Parflow‐CLM [Community Land Model]) of the Upper Ouémé catchment in Benin (14, 000 km 2 ) at a 1‐ × 1‐km 2 resolution. The impact of parameter changes in the near subsurface (0.3‐to‐5‐m depth) and in the deeper regolith aquifer (24‐ and 48‐m maximum depth) was assessed in five modeling experiments. Streamflow was largely dependent on K s and on clay distribution in the near subsurface and less on the properties of the deeper subsurface. Groundwater table depths and amplitudes were controlled by vegetation and topography as observed on instrumented hillslopes and for K s within the literature range. Experiments with higher K s suggested a K s threshold where dynamics become less determined by one‐dimensional vertical and more determined by lateral processes. Such heterogeneity impacts from smaller scales need to be accounted for when hydrological models are upscaled to larger domains (1‐ × 1‐km 2 resolution or coarser). Our findings highlight the need for a new conceptual approach to represent clay distribution in order to develop catchment‐scale CZ models of HRAs in WA that capture the observed processes. Core Ideas: Simulated water balance components for a catchment in West Africa were confirmed by observations. Subsurface (0.3‐to‐5‐m depth) exerts stronger control on streamflow than deeper regolith. K s magnitude determines transition from topography‐ to recharge‐controlled water table dynamics. We identified a limit of K s where the impact of one‐dimensional processes on water table dynamics ceases. A high‐permeability fissured zone at the bottom shows little impact on the simulations.